A study of prevalence and association of risk factors for diabetic vasculopathy in an urban area of Gujarat - Jayesh D Solanki; Amit H Makwana; Hemant B Mehta; Pradnya A Gokhale; Chinmay J Shah (Journal of Family Medicine and Primary Care, 2013)
Background: Peripheral arterial disease (PAD) is an aftermath of type 2 diabetes posing a significant health problem in developing countries. Its silent progression warrants presymptomatic screening by ankle brachial index (ABI), which cannot be applied to the whole population. We tried to measure the burden of PAD in diabetics of this region correlating various risk factors for it quantitatively and qualitatively. Materials and Methods: From various out-patient departments, 110 known under treatment type 2 diabetics were recruited. They underwent thorough assessment for general, symptomatic, medical history and risk factor screening that included 11 well-known risk factors. ABI was measured by Versadop instrument using the standard protocol with ABI <0.9 being considered as abnormal. Results: There was a high prevalence of asymptomatism, hypertension, positive family history and age <52 years in the study group. Relative risk was highest for asymptomatism followed by high body mass index, hyperlipidemia, cardiovascular disease and smoking, but less significant for age, gender, fasting sugar level, family history. More adverse ABI profile was noticed with the increase in number of five modifiable risk factors cumulatively. Conclusion: There was a high prevalence of low ABI in our region that is an evidence of PAD mainly affected by risk factors many of which were modifiable. Defining those who are at risk to develop PAD in Diabetes, one can use ABI better in early screening and prompt treatment of this complication to stop its further progression and primary prevention can be served as felt the need for health-care effectively.